Pedagogical Strategy to Develop Research Competencies in Medical Sciences Teachers (Docentes 2.0 Journal, 2022)
The need of contemporary man to face daily different situations in the personal and professional field has led him to investigate, professionally or not, how to find the best solution to the problems that arise daily. Hence, this article aimed to design a pedagogical strategy to develop investigative skills in Medical Sciences teachers that contributes to professional-pedagogical performance. An investigation was carried out under the historical-logical method, under the pragmatic paradigm, with a hybrid approach of Sequential type with Explanatory design. Of the population established with 67 professors summoned to participate in said research, 35 were chosen, representing 23.45% of the population, an intentional non-probabilistic sample. The results of the instruments after the proposal was applied allowed to recognize the professional and human improvement of the teachers of medical sciences and the development of investigative competencies applied in their professional performance. The teacher-researcher role implies permanent reflection, assuming a critical attitude about what has been learned in their training, and sharing knowledge with their peers and students to establish synergies between what is learned and researched and what is taught and why. The study and the systematization made it possible to determine the theoretical foundations that support the development of investigative competencies in the context of Medical Education and specifically in the Faculty of Medical Sciences of Artemisa.
Keywords: Strategy; pedagogical; skills; research; medical sciences